Kaizen: Right management - Petr Besta; Radim Lenort (Contemporary Economics, 2008)
The article deals with the analysis of the Kaizen principles so called the continual improving principles. It compares the Japanese and European view at the control of the changes. Then the article describes the implementation of Kaizen principles in the companies.
Keywords: 330